Cardiac Surgery Procedures - Montalto, Andrea; Loforte, Antonio; Amarelli, Cristiano (IntechOpen, 2020)
This edited volume Cardiac Surgery Procedures is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field. The book comprises single chapters authored by various researchers and edited by experts active in the research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors and opens new possible research paths for further novel developments.